THE CHALLENGES OF ENGLISH TEACHERS IN REMOTE AREAS TOWARD ONLINE TEACHING DURING COVID-19 PANDEMIC - Niely Fawaidah Virgin; Imam Qalyubi; Zaitun Qamariah (IKIP Siliwangi, 2021)
This study aimed at investigating the challenges and identifying the way the English teachers solve the challenges toward online teaching during Covid-19 pandemic. This study was qualitative research. Three instruments were used to collect the data, those are: open-ended questionnaire, interview and documentation. As a result, this study showed that there were eight challenges experienced by the English teachers in remote areas toward online teaching during Covid-19 pandemic, those are: (1) inadequate infrastructure; (2) student’s learning attention; (3) financial condition; (4) students readiness; (5) parent’s concern; (6) designing materials; (7) measuring student’s understanding, and (8) the instability of student’s motivation. During teaching-learning process, there were various ways in overcoming the challenges done by the English teachers, those are: (1) create an interactive media; (2) decide the most suitable online learning tool; (3) give additional time for the students; (4) provide adequate facilities for both teacher and student in remote areas. Keywords: Challenge, Covid-19 Pandemic, English Teaching, Online Learning